Evaluation of the TRPM2 channel as a biomarker in breast cancer using public databases analysis - Sumoza Toledo, Adriana; Espinoza Gabriel, Mario Iván; Montiel Condado, Dvorak (Hospital Infantil de México, 2016)
Background: Breast cancer is one of the most common malignancies affecting women. Recent investigations have revealed a major role of ion channels in cancer. The transient receptor potential melastatin-2 (TRPM2) is a plasma membrane and lysosomal channel with important roles in cell migration and cell death in immune cells and tumor cells. Methods: In this study, we investigated the prognostic value of TRPM2 channel in breast cancer, analyzing public databases compiled in OncomineTM (Thermo Fisher, Ann Arbor, MI) and online Kaplan-Meier Plotter platforms. Results: The results revealed that TRPM2 mRNA overexpression is significant in situ and invasive breast carcinoma compared to normal breast tissue. Furthermore, multi-gene validation using OncomineTM showed that this channel is coexpressed with proteins related to cellular migration, transformation, and apoptosis. On the other hand, Kaplan-Meier analysis exhibited that low expression of TRPM2 could be used to predict poor outcome in ER- and HER2+ breast carcinoma patients. Conclusions: TRPM2 is a promising biomarker for aggressiveness of breast cancer, and a potential target for the development of new therapies.